PENDAMPINGAN PENDIDIKAN NON FORMAL DI RUMAH TA’LIM AL-QUR’AN DARUL FIRDAUS KEBAYORAN LAMA - Mukhamad Farhan,; Jihad Maulana,; Matnur Ritonga, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
Education can be a benchmark for the progress and quality of life of a nation, so that it can be said that the progress of a nation or country can be achieved, one of which is through improving and structuring good education. realized in the form of the construction of the RTA for the Al-Qur'an Ta'lim House. RTA is an instrument for empowering people who have a very strategic role in improving the quality of spiritual education. Some of the program activities carried out in this service are as follows: a) Organizing learning activities together to read the Koran and holding competitions at RTA Darul Firdaus.